2022
DOI: 10.1038/s41598-022-11070-6
|View full text |Cite
|
Sign up to set email alerts
|

Multispectral pattern recognition measures change in drusen area in age-related macular degeneration with high congruency to expert graders

Abstract: Drusen are a hallmark lesion of age-related macular degeneration (AMD) and changes in their area and/or volume are strongly associated with disease progression. Assessment of longitudinal change in drusen size in clinical practice however is limited to a single commercial tool or manual inspection by clinicians. In this study we analysed change in drusen area in 33 eyes with intermediate AMD across two separate visits using a novel technique known as multispectral pattern recognition for en face retinal images… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Even though it is a great tool for assessing AMD progression, some studies showed decreased sensitivity and specificity of drusen change quantification measured by Cirrus Advanced RPE Analysis when compared to a multispectral pattern recognition change analysis or expert graders. The multispectral pattern recognition change analysis is a multimodal approach assessment that includes fundus autofluorescence, infrared 815 nm, and green 532 nm ophthalmoscopy image scanning [103].…”
Section: Oct Evaluation Of Drusenmentioning
confidence: 99%
“…Even though it is a great tool for assessing AMD progression, some studies showed decreased sensitivity and specificity of drusen change quantification measured by Cirrus Advanced RPE Analysis when compared to a multispectral pattern recognition change analysis or expert graders. The multispectral pattern recognition change analysis is a multimodal approach assessment that includes fundus autofluorescence, infrared 815 nm, and green 532 nm ophthalmoscopy image scanning [103].…”
Section: Oct Evaluation Of Drusenmentioning
confidence: 99%
“…The usual outcome of the non-neovascular type is slow-but-steady progressive vision deterioration, which spans months to years. The first clinical sign might be drusen only, but certain peculiar structural characteristics of drusen are associated with rapid progression to advanced stages of AMD [ 59 ]. The definitive outcome of the non-exudative form is an irreversible distortion of RPE and GA [ 60 ].…”
Section: Reviewmentioning
confidence: 99%
“…It has been applied in some ophthalmic diseases, such as diabetic retinopathy 9 and macular degeneration. 10 Research shows that the reduction of oxygen content in retinal tissue plays a role in the development of many retinal diseases, such as diabetic retinopathy, 11 arteriovenous occlusion, 12 age-related macular degeneration, 13 and glaucoma. 14 Some studies have shown that multispectral fundus imaging technology can be used as a noninvasive means to analyze the oxygen saturation in human retinal and choroidal vessels.…”
mentioning
confidence: 99%